1982
DOI: 10.3758/bf03202435
|View full text |Cite
|
Sign up to set email alerts
|

Instrument inferences and verb schemata

Abstract: Five studies employed a Stroop paradigm to examine the activation of instruments in sentence comprehension. Two types of instruments were studied, tools (e.g., spoon, hammer) and body parts (e.g., hand, wing). For example, is the concept "broom" activated by the sentence "The man swept the floor," or is the concept "wing" activated by the sentence "The duck flew over the pond"? Earlier studies have suggested that implicit instruments are not encoded in the underlying representation of a sentence during compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
55
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 40 publications
5
55
0
Order By: Relevance
“…Whitney's (1986) dissertation extended this work to anaphoric reference. Priming with atypically biasing sentences led to interference in color naming for atypical words, whereas priming with typically biasing sentences led to facilitation for typical words, the latter reminiscent of Dosher and Corbett's (1982) finding. Clearly, word meaning matters; even noncolor words can produce (or increase) interference--or even facilitation--under suitable priming conditions.…”
Section: Semantic Variation and The Irrelevant Wordmentioning
confidence: 73%
See 1 more Smart Citation
“…Whitney's (1986) dissertation extended this work to anaphoric reference. Priming with atypically biasing sentences led to interference in color naming for atypical words, whereas priming with typically biasing sentences led to facilitation for typical words, the latter reminiscent of Dosher and Corbett's (1982) finding. Clearly, word meaning matters; even noncolor words can produce (or increase) interference--or even facilitation--under suitable priming conditions.…”
Section: Semantic Variation and The Irrelevant Wordmentioning
confidence: 73%
“…Merrill et al concluded that good comprehenders encode words with reference to an entire sentence's meaning, whereas poor comprehenders encode the words as distinct units. Dosher and Corbett (1982) examined whether sentences like "The man swept the floor" activated relevant instruments (e.g., broom). If so, then broom should interfere with naming its color of print.…”
Section: Semantic Variation and The Irrelevant Wordmentioning
confidence: 99%
“…Inthe same paper, Burt found facilitation ofcolor naming when primes were identical to targets (but see McClain, 1983). Facilitation of color naming also has been reported in sentencepriming studies in which subjects covertly generated the target word upon sentence presentation (Dosher & Corbett, 1982;Whitney, 1986). In the literature on processing biases in anxiety disorders and phobias, facilitation of color naming has been observed, a result that contrasts with the typical result of retardation of color naming to threat words (Mathews & C. MacLeod, 1985;Mogg, Mathews, & Weinman, 1989;Watts, McKenna, Sharrock, & Trezise, 1986).…”
mentioning
confidence: 59%
“…There is precedent in the literature for inferences being made in paragraphs, rather than in simple sentences. Although readers do not appear to spontaneously infer the instruments implied by actions in simple sentences (Dosher & Corbett, 1982;Singer, 1979), such inferences are made in some longer contexts in which they aid sentence integration (McKoon & Ratcliff, 1981). Because integrating information from two sentences is easier if the antecedent information is specific rather than general (Garrod & Sanford, 1977), instantiation may be useful in sentence integration.…”
Section: Subjectsmentioning
confidence: 99%